Transdiagnostic neuromodulation of impulsivity: current status and future trajectories - Gangliang Zhong; Tianzhen Chen; Na Zhong; Tara Rezapour; Abbas Haghparast; Haifeng Jiang; Hang Su; Tifei Yuan; Trevor William Robbins; Jiang Du; Min Zhao (Translational Psychiatry)
Abstract Impulsivity, increasingly perceived as a transdiagnostic characteristic, significantly influences diverse psychiatric conditions and emanates beyond the boundaries defined by traditional classification systems. Transdiagnostic research has shed light on the complex clinical manifestations of impulsivity, and the underpinning neural circuitry. The pressing challenge now is to translate this enhanced understanding into precise and potent interventions tailored to these different aspects of impulsivity. Recent advancements in neuromodulation, specifically targeting brain circuits, have provided encouraging evidence for improvements in clinical symptoms, and neural circuitry across various psychiatric conditions, signposting a transformative phase in crafting interventions that tackle impulsivity from a transdiagnostic perspective. However, the field continues to ascertain a universally embraced framework that effectively amalgamates these discoveries into a unified clinical methodology. The Research Domain Criteria (RDoC) delivers a neuroscientifically informed framework that aims to reconcile the neurobiological underpinnings with clinical symptoms, thereby facilitating targeted neuromodulation strategies. In this context, we propose a pioneering RDoC-compliant framework that strategically targets the neural circuits implicated in clinical impulsivity symptoms, applicable across diagnostic categories. Furthermore, we introduce a set of meticulously selected tools for each stage within this framework, thus reinforcing its applicability and aiding future investigative pursuits in this area.